Antagonistic Effect of Aspergillus melleus Yukawa on Soilborne Pathogens of Chickpea - F.sara Dolar (Journal of Agricultural Sciences)
Effect of Aspergillus melleus Yukawa on mycelial growth and infection of chickpea by Marcophomina phaseolina, Fusarium oxysporum f. sp. ciceri, F. solani, F. acuminatum, F. equiseti, F. moniliforme, F. sambucinum and Rhizoctonia solani was studied. A. melleus inhibited the colony growth of F. sambucinum, F. equiseti, R. solani, M. phaseolina, F. oxysporum and F. moniliforme 52.2, 51.1, 46.6, 46.6, 46.3 and 42.1%, respectively on PDA. Root rot and wilt diseases caused by F. sambucinum, F. moniliforme, M. phaseolina, F. equiseti and F. oxysporum f. sp. ciceri in A. melleus-amended soil were reduced significantly. However, there was no effect of A. melleus on infection by F. acuminatum and R. solani in chickpea. The highest reduction value was obtained with M. phaseolina 72.78°k .